Survival Analysis of Non-metastatic Triple Negative Breast Cancer Patients in a Tertiary Care Centre in North Karnataka, India - Mehrotra, Kritika; Bhise, Rohan; Doshi, Mrugal (Asian Pacific Journal of Cancer Care, 2025)
Aim: The aim of this study is to examine the demographic and clinicopathological characteristics, treatment modalities, and survival statistics of triple negative breast cancer (TNBC) patients at our institution, along with analysing the correlation between these variables and clinical outcomes. Methodology: A cohort of non-metastatic TNBC patients treated from January 2017 to June 2023 was analysed, utilizing descriptive statistics to report characteristics and employing the cox proportional hazard model for assessing prognostic factors in overall survival (OS) and disease free survival (DFS). Results: Total149 patients underwent analysis, with a median follow-up period of 32.5 months; the mean age was recorded at 47.4 years, 67.7% categorized as premenopausal and 42.28% at stage III. 72% underwent upfront surgery and among those receiving neoadjuvant chemotherapy (NACT), 80.9% achieved a pathological complete response (pCR). At time of analysis, 10% patients had died and 22.8% experienced disease recurrence with 55.8% of recurrences being distant metastasis. The median OS & DFS was 51 months & 47 months with significant differences in OS and DFS noted between stage I/ II and stage III patients. A high ki67 index (>30%) correlated with significantly poorer OS and DFS while specific chemotherapy regimens yielded notable survival rates. Multivariate analysis identified high stage, lymphovascular invasion (LVI), extra nodal extension (ENE) and high ki 67 index as significant poor prognostic factors. Conclusion: TNBC predominantly affects younger women and is diagnosed at advanced stages. Most patients experienced relapse within 3-5 years post-treatment. Identified poor prognostic factors impacting survival include disease stage, LVI, ENE, and high ki-67 index. The relatively short median follow-up in our study, necessitates further studies for a comprehensive understanding of outcomes in survivors.